2020
DOI: 10.51481/amc.v62i2.1063
|View full text |Cite
|
Sign up to set email alerts
|

Barreras y facilitadores relacionados con el diagnóstico de la lepra en Costa Rica

Abstract: Objetivo: analizar barreras y facilitadores relacionados con el diagnóstico de la lepra en Costa Rica, desde la perspectiva de la persona con la enfermedad y en el contexto de la vida cotidiana. Métodos: se llevó a cabo un estudio cualitativo de carácter exploratorio a partir de 25 entrevistas semiestructuradas, a personas con lepra o con antecedente de haberla padecido, de entre 23 y 88 años, atendidos en el sistema de salud público costarricense. A partir del análisis de los datos cualitativos, las bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The lack of health professionals and their lack of training are barriers that hinder guaranteeing quality services in leprosy [ 16 – 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of health professionals and their lack of training are barriers that hinder guaranteeing quality services in leprosy [ 16 – 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this field, we have not found evidence in literature that examines barriers from the perspective of health professionals in leprosy contexts in order to contrast out results. Nonetheless, research has been found in reviews of literature[ 16 , 17 ] or that analyse these barriers from other perspectives, such as that of people affected by leprosy [ 18 20 ] or the community [ 21 ]. Results have also been found in other contexts [ 22 ] or concerning other diseases, such as tuberculosis or HIV [ 23 ].…”
Section: Introductionmentioning
confidence: 99%